Winter thermal structure of Lake Superior. (1st July 2014) - Titze, Daniel J.; Austin, Jay A.
Abstract : Moorings equipped with thermistors that span the water column were deployed at up to seven locations throughout Lake Superior from October 2005 through May 2013. This year‐round, multi‐year, multi‐location, full water‐column record of the thermal structure reveals significant inter‐annual and spatial variability in Lake Superior's winter heat content, thermocline depth, and phenology. There is a stark contrast in thermal structure between the cold, icy winter of 2009, during which strong negative stratification formed, and the much warmer winter of 2012, during which the stratification was much weaker. Significant inter‐annual and spatial variability was also observed in ice cover, which influenced heat content. Ice cover significantly inhibits heat flux between the lake and the atmosphere, and spatial variability in ice cover translates into spatial variability in end‐of‐winter heat content. This is found to be preserved through the spring warming season, and is strongly correlated with variability in the timing of the onset of summer stratification, with regions that have warmer end‐of‐winter water columns stratifying earlier than regions with colder end‐of‐winter water‐columns. Observed spring warming rates appear to depend not on mooring depth, but on regionally averaged depth; this suggests the existence of a lateral mixing mechanism.